2010
DOI: 10.3748/wjg.v16.i25.3133
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab plus FOLFOX6 or FOLFIRI in metastatic colorectal cancer: CECOG trial

Abstract: This study confirms that combinations of cetuximab with FOLFOX6 or FOLFIRI are effective and significantly improve clinical outcome in KRAS wild-type compared with KRAS mutated mCRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 33 publications
7
59
0
Order By: Relevance
“…Our findings may be explained by divergent results obtained for different fluoropyrimidine backbones. Among the available trials, 4 used infusional 5-FU regimens (77)(78)(79)(80), whereas other 3 used either capecitabine or bolus 5-FU as their chemotherapy backbone (81)(82)(83). An interaction between anti-EGFR agents and the mode of fluoropyrimidine application (oral vs. infusional) is currently discussed (84).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may be explained by divergent results obtained for different fluoropyrimidine backbones. Among the available trials, 4 used infusional 5-FU regimens (77)(78)(79)(80), whereas other 3 used either capecitabine or bolus 5-FU as their chemotherapy backbone (81)(82)(83). An interaction between anti-EGFR agents and the mode of fluoropyrimidine application (oral vs. infusional) is currently discussed (84).…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab and panitumumab, two monoclonal antibodies, which neutralize the extracellular domain of EGFR, have demonstrated effectiveness in terms of both response and survival when used as first, second or thirdline chemotherapy. Although anti-EGFR agents are routinely used in clinical practice, their use is limited to 60% of patients who have KRAS wild-type tumors (2) because randomized-controlled studies have shown activating mutations of this oncogene were predictive of resistance to these agents (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in the development of various diagnostic tools, in many patients, colorectal cancer is still diagnosed at an advanced stage, and recurrent tumors are often detected even after curative surgery. On the other hand, new chemotherapeutic regimens such as FOLFOX, FOLFIRI, and XELOX have been developed to exert a more potent activity 3, 4, 5, 6. More recently, molecular targeted therapies such as tyrosine kinase inhibitors and monoclonal antibodies have been shown to enhance tumor regression in combination with chemotherapy 7, 8…”
mentioning
confidence: 99%